Impact of Islamic banks' brand personality (IBBP) on customers' purchase intention : a study of Islamic banks in Malaysia - Ahmed, Muhammad (Kulliyyah of Economics and Management Sciences, International Islamic University Malaysia, 2016)
Given the intense competition and low switching cost, marketers employ several techniques to differentiate their brands from others. Brand personality is one such approach. It facilitates crafting customer-brand relationship, brand image, brand commitment, and most importantly, the purchase intention. Aaker's brand personality model with its five dimensions (sincerity, excitement, competence, sophistication, and ruggedness) has been studied at length especially in the manufacturing sector whereas the service industry has remained understudied. Aaker's model has also been criticized pertaining to the issues such as generalizability across countries and cultures. Considering religion (Islam), an important yet ignored element of culture, this study highlights the criticism on Aaker's framework. Based on Qur'an, hadith and the work of traditional as well as modern Muslim scholars, this research is among the early attempts to develop and validate an Islamic Banks' Brand Personality (IBBP) model in Malaysia. With the help of 388 usable responses in the Klang valley, IBBP model was empirically tested through exploratory factor analysis (EFA) followed by the confirmatory factor analysis (CFA). Two new dimensions (Trust_Just and Shariah Compliance) emerged along with the four existing dimensions. Interestingly, Trust_Just obtained the highest percentage of variance i.e. 42.106 per cent. In order to examine the impact of IBBP on customers' purchase intention, theory of planned behaviour (TPB) was employed and subsequently tested using structural equations modeling (SEM). Out of the ten hypothesized relationships, nine were supported. Findings of this research revealed that IBBP has a positive impact on brand attitude, subjective norms and perceived behavioural control. Similarly, brand attitude, subjective norms, and perceived behavioural control positively affect purchase intention. However, the direct relationship between IBBP and purchase intention was not significant. Therefore, the relationship between IBBP and purchase intention was fully mediated by brand attitude, subjective norms and perceived behavioural control. The findings of this research are significant for the Islamic banking industry. With the help of IBBP, Islamic banks can create a better brand image, employ advertising strategies effectively, and ultimately retain the existing and attract the potential customers with higher purchases as well as re-purchases. This research contributes to the literature of Islamic branding, hence benefitting academicians. Practitioners and policy makers can also benefit from the results of this research.